2002
DOI: 10.1104/pp.001867
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of CLV3 Expression by Two Homeobox Genes in Arabidopsis

Abstract: The ability of meristems to continuously produce new organs depends on the activity of their stem cell populations, which are located at the meristem tip. In Arabidopsis, the size of the stem cell domain is regulated by two antagonistic activities. The WUS (WUSCHEL) gene, encoding a homeodomain protein, promotes the formation and maintenance of stem cells. These stem cells express CLV3 (CLAVATA3), and signaling of CLV3 through the CLV1/CLV2 receptor complex restricts WUS activity. Homeostasis of the stem cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
208
2
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(234 citation statements)
references
References 18 publications
22
208
2
2
Order By: Relevance
“…At present, our results cannot distinguish if downregulation of RBR or the resulting loss of cell-cell contact between L1 and L2 disrupts the CLV-WUS feedback loop, which maintains the SAM stem cell niche that contributes to meristem activity and primordia formation (Brand et al, 2000(Brand et al, , 2002Rojo et al, 2002;Tucker and Laux, 2007). Loss of CLV3 activity leads to gradual conversion of bordering cells in the SAM peripheral zone to cells with central zone characteristics , suggesting that CLV3 is involved in a signaling pathway required for the switch from stemness to differentiated cells.…”
Section: Rbr Homeostasis Is Critical For Meristem Integrity and Functionmentioning
confidence: 86%
See 1 more Smart Citation
“…At present, our results cannot distinguish if downregulation of RBR or the resulting loss of cell-cell contact between L1 and L2 disrupts the CLV-WUS feedback loop, which maintains the SAM stem cell niche that contributes to meristem activity and primordia formation (Brand et al, 2000(Brand et al, , 2002Rojo et al, 2002;Tucker and Laux, 2007). Loss of CLV3 activity leads to gradual conversion of bordering cells in the SAM peripheral zone to cells with central zone characteristics , suggesting that CLV3 is involved in a signaling pathway required for the switch from stemness to differentiated cells.…”
Section: Rbr Homeostasis Is Critical For Meristem Integrity and Functionmentioning
confidence: 86%
“…Histological Analysis, GUS Staining, DAPI Staining, and Microscopy GUS staining was performed as described by Brand et al (2002). For histological analysis, samples were fixed in 4% formaldehyde, 50% ethanol, and 10% acetic acid overnight at 48C.…”
Section: Ploidy Analysismentioning
confidence: 99%
“…The deletions of pCLV3 were derived from the CLV3 promoter (SI Experimental Procedures) as described in an earlier study (31,35). Details on the constructs used for expression and phenotypic complementation analysis of the mutant CLV3 promoter and the misexpression of eGFP-WUS, NLS-eGFP-WUS, and Dex-inducible amiRNA for WUS silencing are given in SI Experimental Procedures.…”
Section: Methodsmentioning
confidence: 99%
“…CLV3, a secreted peptide, activates a receptor kinase pathway to restrict WUS transcription (6)(7)(8)(9). Previous studies have shown that ectopic activation of WUS in the central zone leads to meristem overproliferation (10,11). Conversely, the depletion of WUS leads to premature differentiation of stem cell progeny (11)(12)(13), showing the importance of the regulation of WUS protein levels.…”
mentioning
confidence: 99%